2019
DOI: 10.1352/1944-7558-124.3.248
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Hypertensive Medication Use and Factors Related to Adherence Among Adults With Intellectual and Developmental Disabilities

Abstract: Adults with intellectual and developmental disabilities (IDD) are known to experience significant health disparities; however, few studies have described anti-hypertensive medication adherence in this population. Using administrative data from South Carolina from 2000–2014, we evaluated the odds of adherence to anti-hypertensive medication among a cohort of adults with IDD and hypertension. Approximately half (49.5%) of the study cohort were adherent to anti-hypertensive medication. Those who lived in a superv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Our findings are consistent with two studies regarding people with intellectual and developmental disabilities, one which explored predictors of low adherence to antihypertensive medication (Cyrus et al, 2019), and the other explored low adherence to psychotropic medication for MI (Tan et al, 2015). The Cyrus paper found residency to be a predictor, but the Tan paper did not examine residence type.…”
Section: Consistency With the Literaturesupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings are consistent with two studies regarding people with intellectual and developmental disabilities, one which explored predictors of low adherence to antihypertensive medication (Cyrus et al, 2019), and the other explored low adherence to psychotropic medication for MI (Tan et al, 2015). The Cyrus paper found residency to be a predictor, but the Tan paper did not examine residence type.…”
Section: Consistency With the Literaturesupporting
confidence: 91%
“…That research has established age, sex, race, patient-physician relationship, cognitive factors, and health care system characteristics as risk factors that can affect antihypertensive medication adherence (Cho et al, 2018; Lewis et al, 2012; Ritchey et al, 2016; Williams et al, 2018; Zolnierek and Dimatteo, 2009). For adults with intellectual and developmental disabilities, one study found that older age, living in a supervised residence, and white race were all associated with higher adherence to antihypertensive medication (Cyrus et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of health disparities in patients with IDD includes suboptimal management of chronic diseases, such as diabetes 18 and hypertension, 19 despite contact with a primary care physician. Nonadherence to a medication regimen might be more common in patients who live with their family or in a residential setting where there is a lower degree of supervision-that is, compared to a residence that maintains 24-hour staffing with daily nursing care and supervision.…”
Section: Management Of Chronic Diseasementioning
confidence: 99%
“…2 While this was an example in spinal cord injury, this experience is common across disability groups. [3][4][5][6][7][8] Given the broad health needs, it is not surprising that people with disabilities take many of medications. People with stroke average 11.3 medications, 9 people with multiple sclerosis average 5.7 medications, 5 and people with arthritis average 5.5 medications.…”
Section: Introductionmentioning
confidence: 99%
“…2 Much like the general population, people with disabilities also have difficulty taking their medications as prescribed. Medication adherence rates are estimated at 49.5% for people with intellectual disability, 4 65.6% for people with stroke, 3 60-80% for people with multiple sclerosis, 8 and 60-80% for people with arthritis. 7 Despite the significant number of people with disabilities, the importance of adherence to medication, and the rates of poor adherence in these populations, disabilityspecific diagnoses are not often studied.…”
Section: Introductionmentioning
confidence: 99%